(untitled) (Journal of Hama University, 2019)
The objective of this study is to determine the impact of credit risk on the solvency of private commercial banks listed on Damascus Stock Exchange, The financial statements (budgets and annual financial reports of private commercial banks) are published on the Damascus Securities Exchange during the period of study (2017-2010), and then analyzed using the simple regression analysis method and the Pearson correlation coefficient and the analysis using SPSS24 to reach the results. The study shows that there is a statistically significant impact of credit risk on the solvency of private commercial banks listed on the Damascus Securities Exchange. This necessitates private commercial banks to increase their financial solvency to suit their credit risk, Credit risk has increased significantly during the study years of 2017-2010 and the financial solvency has a significant impact on the stability of the banking environment. It plays an effective role in maintaining the soundness and soundness of banking systems and strengthening their financial position.